Metrics and Models for Evaluating the Quality and Effectiveness of ERP Software - Muketha, Geoffrey Muchiri; Muketha, Geoffrey Muchiri, 1970-; Micheni, Elyjoy Muthoni, 1963- (USA: IGI Global, 2020)
"This book presents theoretical measurement models and metrics for measuring software size and complexity of large scale enterprise resource planning software. It focuses on the relationship between software complexity and quality with the aim of controlling quality and on enterprise resource planning development, performance, challenges, and even success stories"--
Includes bibliographical references (pages 343-383) and index.
Keywords: Enterprise resource planning -- Data processing; Manufacturing resource planning -- Data processing; Computer software -- Evaluation